Clinical results by using anti-inflammatory and local anesthetic drug for the treatment of muccosites in oncological patients who received the combined treatment - Коленко, Ю. Г.; Ліновицька, О. В.; Тимохіна, Т. О.; Сінько, А. О. (Actual Dentistry, 2020)
Purpose of the study. Improving the effectiveness of methods of prevention and treatment of oral mucositis in cancer patients by using the drug «Tantum Verde®». Materials and methods. The study included 77 patients with squamous cell carcinoma of the oropharyngeal region of stage I–IV. All patients received radiation or chemoradiotherapy. The average age of patients was 51±6.3 years. Research results. The following results were obtained: 1) the level of caries intensity in all groups of patients was high; 2) the level of prevalence and intensity of periodontal diseases in accordance with the CPITN index in all groups corresponded to the indicator of the need for all patients in conducting professional oral hygiene and teaching individual oral hygiene; 3) the degree of inflammatory diseases in the gum tissue on average corresponded to gingivitis of moderate severity; 4) the level of individual oral hygiene met with unsatisfactory indicators. Conclusion. The use of methods for the prevention and treatment of mucositis, based on the use of the drug «Tantu m Verde®», is more effective compared to traditional methods of treatment. When assessing the severity of mucositis, patients receive treatment using this drug with intensity indicators 73.5 %, 71.3 % and 30.6 % lower than patients who do not use this drug (p < 0.05). Key words: Tantum Verde®, mucossitis, complex treatment.